PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL), DAN BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP PROFITABILITAS (ROA) PADA BANK PERKREDITAN RAKYAT DI KOTA SEMARANG (Students' Journal of Accounting and Banking, 2013)
The purpose of this research was to determine the influences of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and BOPO to Profitability Return On Assets (ROA) at in the Semarang City. The population in this research are all rural banks in Semarang with samples totaling 19 BPR. Aspects researched are the financial statements of the period December 2011-September 2012. Data collection techniques in this study using the census was taken. There research variables are CAR, LDR, NPL, and BOPO as independent variables and Profitability, as measured by ROA as a bound variable. Data taken with the metod of documentation. The data obtained were analyzed using multiple regression analysis. Results significance test using a significance level of 0,005 obtained 0,000 significance. Because of the significance level of less than 0,005 then CAR simultaneously, LDR, NPL, and BOPO effect Profitability (ROA) at BPR in the Semarang City. Hypothesis testing results partially CAR, LDR, and NPL has no significances effect on Profitability, whereas the significance effect on Probability BOPO. The amount of simultaneous influence CAR, LDR, NPL, and BOPO to Profitability (ROA) was 67,2%. While the rest influenced by other variables not examined. Keywords: CAR, LDR, NPL, BOPO, Profitability (ROA).